Optimal control of a switched reluctance drive by a direct method using a discrete variational principle - Flasskamp, Kathrin; Ober-Blobaum, Sina; Schneider, Tobias; Bocker, Joachim (52nd IEEE Conference on Decision and Control)

Control strategies on stable manifolds for energy-efficient swing-ups of double pendula - Flaßkamp, Kathrin; Timmermann, Julia; Ober-Blöbaum, Sina; Trächtler, Ansgar (International Journal of Control)

Methods for the Design and Development - Anacker, Harald; Dellnitz, Michael; Flaßkamp, Kathrin; Groesbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Horenkamp, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Korf, Sebastian; Krüger, Martin; Müller, Wolfgang; et al. (Lecture Notes in Mechanical Engineering)

Optimierte 3D Morphologiedarstellung tomographischer Datensätze des Herzens - Arens, S.; Domik, Gitta; Weise, R.; Holzinger, J.; Burchert, W.

Das Praktikum – Rechte und Pflichten eines arbeitsrechtlichen Rechtsverhältnisses - Krimphove, Dieter (Betriebs-Berater)

Neues zur Geltung nicht umgesetzter europäischer Richtlinien - Krimphove, Dieter (EuZW)

Rechtsfragen der Rekrutierung ausländischen Personals - Krimphove, Dieter; Lüke, Christoph (Betriebs-Berater)

Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics, ALGOSENSORS 2013

Symmetry-Selective Third-Harmonic Generation from Plasmonic Metacrystals - Chen, Shumei; Li, Guixin; Zeuner, Franziska; Wong, Wing Han; Pun, Edwin Yue Bun; Zentgraf, Thomas; Cheah, Kok Wai; Zhang, Shuang (Physical Review Letters)

Hochauflösende Holografie - Zentgraf, Thomas (Physik in unserer Zeit)

The computation of convex invariant sets via Newton's method - Baier, Robert; Dellnitz, Michael; Hessel-von Molo, Mirko; Sertl, Stefan; Kevrekidis, Ioannis G. (Journal of Computational Dynamics)

Variational Lie Group Formulation of Geometrically Exact Beam Dynamics: Synchronous and Asynchronous Integration - Leitz, Thomas; Ober-Blöbaum, Sina; Leyendecker, Sigrid (Multibody Dynamics)

On the role of quadrature rules and system dimensions in variational multirateintegrators - Gail, Tobias; Leyendecker, Sigrid; Ober-Blöbaum, Sina (The 3rdJoint International Conference on Multibody System Dynamics)

Variational formulation and structure-preserving discretization ofnonlinear electric circuits - Ober-Blöbaum, Sina; Lindhorst, Henning (21st International Symposium on Mathematical Theory of Networks and Systems)

Interview with Michael Rosemann on ambidextrous business process management - Kohlborn, Thomas; Müller, Oliver; Poeppelbuss, Jens; Roeglinger, Maximilian (Business Process Management Journal)

Handbuch für offene gesellschaftliche Innovation - Raffl, Celina; Lucke, Jörn; Müller, Oliver; Zimmermann, Hans-Dieter; Vom Brocke, Jan (TOGI-Schriftenreihe)

Identifying and characterizing topics in enterprise content management: a latent semantic analysis of vendor case studies - Herbst, Andrea; Simons, Alexander; vom Brocke, Jan; Müller, Oliver; Debortoli, Stefan; Vakulenko, Svitlana (European Conference on Information Systems)

Identifying the role of information systems in achieving energy-related environmental sustainability using text mining - Reuter, Nadine; Vakulenko, Svitlana; vom Brocke, Jan; Debortoli, Stefan; Müller, Oliver (European Conference on Information Systems)

How In-memory Technology Can Create Business Value: Insights from the Hilti Case - vom Brocke, Jan; Debortoli, Stefan; Müller, Oliver; Reuter, Nadine (Communications of the Association for Information Systems)

A Novel Technique and its Application to Computer Go - Schaefers, Lars; Platzner, Marco (IEEE Transactions on Computational Intelligence and AI in Games)

An FPGA-based Reconfigurable Mesh Many-Core - Giefers, Heiner; Platzner, Marco (IEEE Transactions on Computers)

FPGA Redundancy Configurations: An Automated Design Space Exploration - Anwer, Jahanzeb; Platzner, Marco; Meisner, Sebastian (Reconfigurable Architectures Workshop (RAW))

Echtzeit Klassifikation von sEMG Signalen mit einem low-cost DSP Evaluation Board - Bockhorn, Arne

A computer vision-based approach to high density EMG pattern recognition using structural similarity - Boschmann, Alexander; Platzner, Marco (Proc. MyoElectric Controls Symposium (MEC))

Towards robust HD EMG pattern recognition: Reducing electrode displacement effect using structural similarity - Boschmann, Alexander; Platzner, Marco (Proc. IEEE Int. Conf. Eng. Med. Biolog. (EMBC))

A Generalized Loop Accelerator Implemented as a Coarse-Grained Array - Brand, Marcel

Easy-to-use-on-the-fly binary program acceleration on many-cores - Damschen, Marvin

Lookup Table Partial Reconfiguration for an Evolvable Hardware Classifier System - Glette, Kyrre; Kaufmann, Paul (IEEE Congress on Evolutionary Computation (CEC))

Entwicklung einer codegrößenoptimierten Softwarebibliothek für 8-Bit Mikrocontroller in netzunabhängigen Notleuchten - Hagedorn, Christoph

A hardware/software infrastructure for performance monitoring on LEON3 multicore platforms - Ho, Nam; Kaufmann, Paul; Platzner, Marco (24th Intl. Conf. on Field Programmable Logic and Applications (FPL))
Keywords: Linux; hardware-software codesign; multiprocessing systems; parallel processing; LEON3 multicore platform; Linux kernel; PMU; hardware counters; hardware-software infrastructure; high performance embedded computing; perf_event; performance monitoring unit; Computer architecture; Hardware; Monitoring; Phasor measurement units; Radiation detectors; Registers; Software

Towards self-adaptive caches: A run-time reconfigurable multi-core infrastructure - Ho, Nam; Kaufmann, Paul; Platzner, Marco (2014 IEEE Intl. Conf. on Evolvable Systems (ICES))
Keywords: Linux; cache storage; embedded systems; granular computing; multiprocessing systems; reconfigurable architectures; Leon3 SPARe processor; custom logic events; evolvable-self-adaptable processor cache; fine granular profiling; integer unit events; measurement infrastructure; microarchitectural events; multicore embedded system; perf_event standard Linux performance measurement interface; processor properties; run-time reconfigurable memory-to-cache address mapping engine; run-time reconfigurable multicore infrastructure; split-level caching; Field programmable gate arrays; Frequency locked loops; Irrigation; Phasor measurement units; Registers; Weaving

EMG-basierte simultane und proportionale Online-Steuerung einer virtuellen Prothese - König, Fabian

Hardware Acceleration of Mechatronic Controllers on a Zynq Platform FPGA - Koch, Benjamin

Advanced AES-key recovery from decayed RAM using multi-threading and FPGAs - Mittendorf, Robert

The Xilinx Zynq Architecture as a Platform for Reconfigurable Heterogeneous Multi-Cores - Rüthing, Christoph

Parallel Monte-Carlo Tree Search for HPC Systems and its Application to Computer Go - Schäfers, Lars
Monte-Carlo Tree Search (MCTS) is a class of simulation-based search algorithms. It brought about great success in the past few years regarding the evaluation of deterministic two-player games such as the Asian board game Go. In this thesis, we present a parallelization of the most popular MCTS variant for large HPC compute clusters that efficiently shares a single game tree representation in a distributed memory environment and scales up to 128 compute nodes and 2048 cores. It is hereby one of the most powerful MCTS parallelizations to date. In order to measure the impact of our parallelization on the search quality and remain comparable to the most advanced MCTS implementations to date, we implemented it in a state-of-the-art Go engine Gomorra, making it competitive with the strongest Go programs in the world. We further present an empirical comparison of different Bayesian ranking systems when being used for predicting expert moves for the game of Go and introduce a novel technique for automated detection and analysis of evaluation uncertainties that show up during MCTS searches.

Optimizing the Generator Start-up Sequence After a Power System Blackout - Shen, Cong; Kaufmann, Paul; Braun, Martin (IEEE Power and Energy Society General Meeting (IEEE GM))

A New Distribution Network Reconfiguration and Restoration Path Selection Algorithm - Shen, Cong; Kaufmann, Paul; Braun, Martin (Power Systems Computation Conference (PSCC))

Multithreaded Parallelization of Mechatronic Controllers on a Zynq Platform FPGA - Surmund, Sebastian

Applications of Evolutionary Computation - 17th European Conference, EvoApplications - I. Esparcia-Alcázar, Anna; Eiben, A.E.; Agapitos, Alexandros; Simões, Anabela; G.B. Tettamanzi, Andrea; Della Cioppa, Antonio; M. Mora, Antonio; Cotta, Carlos; Tarantino, Ernesto; Haasdijk, Evert; Divina, Federico; Fernández de Vega, Francisco; et al.

Analytic reliability evaluation for fault-tolerant circuit structures on FPGAs - Anwer, Jahanzeb; Platzner, Marco (IEEE International Symposium on Defect and Fault Tolerance in VLSI and Nanotechnology Systems (DFT))

Fast process variation analysis in nano-scaled technologies using column-wise sparse parameter selection - Ghasemzadeh Mohammadi, Hassan; Gaillardon, Pierre-Emmanuel; Yazdani, Majid; De Micheli, Giovanni (2014 IEEE/ACM International Symposium on Nanoscale Architectures (NANOARCH))

The deep structure of organizational online networking - an actor-oriented case study - Trier, Matthias; Richter, Alexander (Information Systems Journal)

Spectral Noise Tracking for Improved Nonstationary Noise Robust ASR - Chinaev, Aleksej; Puels, Marc; Haeb-Umbach, Reinhold (11. ITG Fachtagung Sprachkommunikation (ITG 2014))
"A method for nonstationary noise robust automatic speech recognition (ASR) is to first estimate the changing noise statistics and second clean up the features prior to recognition accordingly. Here, the first is accomplished by noise tracking in the spectral domain, while the second relies on Bayesian enhancement in the feature domain. In this way we take advantage of our recently proposed maximum a-posteriori based (MAP-B) noise power spectral density estimation algorithm, which is able to estimate the noise statistics even in time-frequency bins dominated by speech. We show that MAP-B noise tracking leads to an improved noise model estimate in the feature domain compared to estimating noise in speech absence periods only, if the bias resulting from the nonlinear transformation from the spectral to the feature domain is accounted for. Consequently, ASR results are improved, as is shown by experiments conducted on the Aurora IV database."

Source Counting in Speech Mixtures Using a Variational EM Approach for Complexwatson Mixture Models - Drude, Lukas; Chinaev, Aleksej; Tran Vu, Dang Hai; Haeb-Umbach, Reinhold (39th International Conference on Acoustics, Speech and Signal Processing (ICASSP 2014))
"In this contribution we derive a variational EM (VEM) algorithm for model selection in complex Watson mixture models, which have been recently proposed as a model of the distribution of normalized microphone array signals in the short-time Fourier transform domain. The VEM algorithm is applied to count the number of active sources in a speech mixture by iteratively estimating the mode vectors of the Watson distributions and suppressing the signals from the corresponding directions. A key theoretical contribution is the derivation of the MMSE estimate of a quadratic form involving the mode vector of the Watson distribution. The experimental results demonstrate the effectiveness of the source counting approach at moderately low SNR. It is further shown that the VEM algorithm is more robust w.r.t. used threshold values."

Towards Online Source Counting in Speech Mixtures Applying a Variational EM for Complex Watson Mixture Models - Drude, Lukas; Chinaev, Aleksej; Tran Vu, Dang Hai; Haeb-Umbach, Reinhold (14th International Workshop on Acoustic Signal Enhancement (IWAENC 2014))
This contribution describes a step-wise source counting algorithm to determine the number of speakers in an offline scenario. Each speaker is identified by a variational expectation maximization (VEM) algorithm for complex Watson mixture models and therefore directly yields beamforming vectors for a subsequent speech separation process. An observation selection criterion is proposed which improves the robustness of the source counting in noise. The algorithm is compared to an alternative VEM approach with Gaussian mixture models based on directions of arrival and shown to deliver improved source counting accuracy. The article concludes by extending the offline algorithm towards a low-latency online estimation of the number of active sources from the streaming input data.
Keywords: Accuracy; Acoustics; Estimation; Mathematical model; Soruce separation; Speech; Vectors; Bayes methods; Blind source separation; Directional statistics; Number of speakers; Speaker diarization

Iterative Bayesian Word Segmentation for Unspuervised Vocabulary Discovery from Phoneme Lattices - Heymann, Jahn; Walter, Oliver; Haeb-Umbach, Reinhold; Raj, Bhiksha (39th International Conference on Acoustics, Speech and Signal Processing (ICASSP 2014))
"In this paper we present an algorithm for the unsupervised segmentation of a lattice produced by a phoneme recognizer into words. Using a lattice rather than a single phoneme string accounts for the uncertainty of the recognizer about the true label sequence. An example application is the discovery of lexical units from the output of an error-prone phoneme recognizer in a zero-resource setting, where neither the lexicon nor the language model (LM) is known. We propose a computationally efficient iterative approach, which alternates between the following two steps: First, the most probable string is extracted from the lattice using a phoneme LM learned on the segmentation result of the previous iteration. Second, word segmentation is performed on the extracted string using a word and phoneme LM which is learned alongside the new segmentation. We present results on lattices produced by a phoneme recognizer on the WSJCAM0 dataset. We show that our approach delivers superior segmentation performance than an earlier approach found in the literature, in particular for higher-order language models. "

Coordinate Mapping Between an Acoustic and Visual Sensor Network in the Shape Domain for a Joint Self-Calibrating Speaker Tracking - Jacob, Florian; Haeb-Umbach, Reinhold (11. ITG Fachtagung Sprachkommunikation (ITG 2014))
"Several self-localization algorithms have been proposed, that determine the positions of either acoustic or visual sensors autonomously. Usually these positions are given in a modality specific coordinate system, with an unknown rotation, translation and scale between the different systems. For a joint audiovisual tracking, where the different modalities support each other, the two modalities need to be mapped into a common coordinate system. In this paper we propose to estimate this mapping based on audiovisual correlates, i.e., a speaker that can be localized by both, a microphone and a camera network separately. The voice is tracked by a microphone network, which had to be calibrated by a self-localization algorithm at first, and the head is tracked by a calibrated camera network. Unlike existing Singular Value Decomposition based approaches to estimate the coordinate system mapping, we propose to perform an estimation in the shape domain, which turns out to be computationally more efficient. Simulations of the self-localization of an acoustic sensor network and a following coordinate mapping for a joint speaker localization showed a significant improvement of the localization performance, since the modalities were able to support each other."

A New Observation Model in the Logarithmic Mel Power Spectral Domain for the Automatic Recognition of Noisy Reverberant Speech - Leutnant, Volker; Krueger, Alexander; Haeb-Umbach, Reinhold (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
In this contribution we present a theoretical and experimental investigation into the effects of reverberation and noise on features in the logarithmic mel power spectral domain, an intermediate stage in the computation of the mel frequency cepstral coefficients, prevalent in automatic speech recognition (ASR). Gaining insight into the complex interaction between clean speech, noise, and noisy reverberant speech features is essential for any ASR system to be robust against noise and reverberation present in distant microphone input signals. The findings are gathered in a probabilistic formulation of an observation model which may be used in model-based feature compensation schemes. The proposed observation model extends previous models in three major directions: First, the contribution of additive background noise to the observation error is explicitly taken into account. Second, an energy compensation constant is introduced which ensures an unbiased estimate of the reverberant speech features, and, third, a recursive variant of the observation model is developed resulting in reduced computational complexity when used in model-based feature compensation. The experimental section is used to evaluate the accuracy of the model and to describe how its parameters can be determined from test data.
Keywords: computational complexity; reverberation; speech recognition; automatic speech recognition; background noise; clean speech; computational complexity; energy compensation; logarithmic mel power spectral domain; mel frequency cepstral coefficients; microphone input signals; model-based feature compensation schemes; noisy reverberant speech automatic recognition; noisy reverberant speech features; reverberation; Atmospheric modeling; Computational modeling; Noise; Noise measurement; Reverberation; Speech; Vectors; Model-based feature compensation; observation model for reverberant and noisy speech; recursive observation model; robust automatic speech recognition

An Overview of Noise-Robust Automatic Speech Recognition - Li, Jinyu; Deng, Li; Gong, Yifan; Haeb-Umbach, Reinhold (IEEE Transactions on Audio, Speech and Language Processing)
New waves of consumer-centric applications, such as voice search and voice interaction with mobile devices and home entertainment systems, increasingly require automatic speech recognition (ASR) to be robust to the full range of real-world noise and other acoustic distorting conditions. Despite its practical importance, however, the inherent links between and distinctions among the myriad of methods for noise-robust ASR have yet to be carefully studied in order to advance the field further. To this end, it is critical to establish a solid, consistent, and common mathematical foundation for noise-robust ASR, which is lacking at present. This article is intended to fill this gap and to provide a thorough overview of modern noise-robust techniques for ASR developed over the past 30 years. We emphasize methods that are proven to be successful and that are likely to sustain or expand their future applicability. We distill key insights from our comprehensive overview in this field and take a fresh look at a few old problems, which nevertheless are still highly relevant today. Specifically, we have analyzed and categorized a wide range of noise-robust techniques using five different criteria: 1) feature-domain vs. model-domain processing, 2) the use of prior knowledge about the acoustic environment distortion, 3) the use of explicit environment-distortion models, 4) deterministic vs. uncertainty processing, and 5) the use of acoustic models trained jointly with the same feature enhancement or model adaptation process used in the testing stage. With this taxonomy-oriented review, we equip the reader with the insight to choose among techniques and with the awareness of the performance-complexity tradeoffs. The pros and cons of using different noise-robust ASR techniques in practical application scenarios are provided as a guide to interested practitioners. The current challenges and future research directions in this field is also carefully analyzed.
Keywords: Speech recognition; compensation; distortion modeling; joint model training; noise; robustness; uncertainty processing

An Evaluation of Unsupervised Acoustic Model Training for a Dysarthric Speech Interface - Walter, Oliver; Despotovic, Vladimir; Haeb-Umbach, Reinhold; Gemmeke, Jrt; Ons, Bart; Van hamme, Hugo (INTERSPEECH 2014)
In this paper, we investigate unsupervised acoustic model training approaches for dysarthric-speech recognition. These models are first, frame-based Gaussian posteriorgrams, obtained from Vector Quantization (VQ), second, so-called Acoustic Unit Descriptors (AUDs), which are hidden Markov models of phone-like units, that are trained in an unsupervised fashion, and, third, posteriorgrams computed on the AUDs. Experiments were carried out on a database collected from a home automation task and containing nine speakers, of which seven are considered to utter dysarthric speech. All unsupervised modeling approaches delivered significantly better recognition rates than a speaker-independent phoneme recognition baseline, showing the suitability of unsupervised acoustic model training for dysarthric speech. While the AUD models led to the most compact representation of an utterance for the subsequent semantic inference stage, posteriorgram-based representations resulted in higher recognition rates, with the Gaussian posteriorgram achieving the highest slot filling F-score of 97.02%. Index Terms: unsupervised learning, acoustic unit descriptors, dysarthric speech, non-negative matrix factorization

Adaptive load allocation for combining Anomaly Detectors using controlled skips - Berger, Mario; Erlacher, Felix; Sommer, Christoph; Dressler, Falko (2014 International Conference on Computing, Networking and Communications (ICNC))

Towards an Open Source IEEE 802.11p stack: A full SDR-based transceiver in GNU Radio - Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Dressler, Falko (2013 IEEE Vehicular Networking Conference)

Timings matter - Bloessl, Bastian; Puschmann, Andre; Sommer, Christoph; Dressler, Falko (Proceedings of the 9th ACM international workshop on Wireless network testbeds, experimental evaluation and characterization - WiNTECH '14)

Towards a vehicular cloud - using parked vehicles as a temporary network and storage infrastructure - Dressler, Falko; Handle, Philipp; Sommer, Christoph (Proceedings of the 2014 ACM international workshop on Wireless and mobile technologies for smart cities - WiMobCity '14)

Towards a simulation framework for paraglider networks - Eckert, Juergen; Sommer, Christoph; Eckhoff, David (Proceedings of the 11th ACM symposium on Performance evaluation of wireless ad hoc, sensor, & ubiquitous networks - PE-WASUN '14)

SmartRevoc: An efficient and privacy preserving revocation system using parked vehicles - Eckhoff, David; Dressler, Falko; Sommer, Christoph (38th Annual IEEE Conference on Local Computer Networks)

Driving for Big Data? Privacy Concerns in Vehicular Networking - Eckhoff, David; Sommer, Christoph (IEEE Security & Privacy)

On the impact of street width on 5.9 GHz radio signal propagation in vehicular networks - Erlacher, Felix; Klingler, Florian; Sommer, Christoph; Dressler, Falko (2014 11th Annual Conference on Wireless On-demand Network Systems and Services (WONS))

The Role of Parked Cars in Content Downloading for Vehicular Networks - Malandrino, Francesco; Casetti, Claudio; Chiasserini, Carla-Fabiana; Sommer, Christoph; Dressler, Falko (IEEE Transactions on Vehicular Technology)

Short paper: Vehicle shadowing distribution depends on vehicle type: Results of an experimental study - Segata, Michele; Bloessl, Bastian; Joerer, Stefan; Sommer, Christoph; Lo Cigno, Renato; Dressler, Falko (2013 IEEE Vehicular Networking Conference)

Towards energy efficient smart phone applications: Energy models for offloading tasks into the cloud - Segata, Michele; Bloessl, Bastian; Sommer, Christoph; Dressler, Falko (2014 IEEE International Conference on Communications (ICC))

A networking perspective on self-organizing intersection management - Sommer, Christoph; Hagenauer, Florian; Dressler, Falko (2014 IEEE World Forum on Internet of Things (WF-IoT))

A cluster based architecture for intersection collision avoidance using heterogeneous networks - Tung, Lung-Chih; Mena, Jorge; Gerla, Mario; Sommer, Christoph (2013 12th Annual Mediterranean Ad Hoc Networking Workshop (MED-HOC-NET))

FAST-BIST: Faster-than-at-Speed BIST Targeting Hidden Delay Defects - Hellebrand, Sybille; Indlekofer, Thomas; Kampmann, Matthias; A. Kochte, Michael; Liu, Chang; Wunderlich, Hans-Joachim (IEEE International Test Conference (ITC'14))

What influences dwell time during source code reading?: analysis of element type and frequency as factors - Busjahn, Teresa; Bednarik, Roman; Schulte, Carsten (ETRA)

Eye tracking in computing education - Busjahn, Teresa; Schulte, Carsten; Sharif, Bonita; Begel, Andrew; Hansen, Michael; Bednarik, Roman; Orlov, Paul; Ihantola, Petri; Shchekotova, Galina; Antropova, Maria (ICER)

Developing Coding Schemes for Program Comprehension using Eye Movements - Busjahn, Teresa; Schulte, Carsten; Kropp, Edna (PPIG)

Proceedings of the 9th Workshop in Primary and Secondary Computing Education, WiPSCE 2014, Berlin, Germany, November 5-7, 2014

Optical Spectroscopy of Graphene Quantum Dots: The Case of C132 - Riesen, Hans; Wiebeler, Christian; Schumacher, Stefan (The Journal of Physical Chemistry A)

Quantum Yields and Reaction Times of Photochromic Diarylethenes: Nonadiabatic Ab Initio Molecular Dynamics for Normal- and Inverse-Type - Wiebeler, Christian; Schumacher, Stefan (The Journal of Physical Chemistry A)

Formation and control of transverse patterns in a quantum fluid of microcavity polaritons - Lewandowski, P.; Ardizzone, V.; Tse, Y. C.; Kwong, N. H.; Luk, M. H.; Lücke, A.; Abbarchi, M.; Bloch, J.; Baudin, E.; Galopin, E.; Lemaître, A.; Leung, P. T.; et al. (Ultrafast Phenomena and Nanophotonics XVIII)

Revisiting SSL/TLS Implementations: New Bleichenbacher Side Channels and Attacks - Meyer, Christopher; Somorovsky, Juraj; Weiss, Eugen; Schwenk, Jörg; Schinzel, Sebastian; Tews, Erik (23rd USENIX Security Symposium (USENIX Security 14))

RESOLVE: An Emotion Word Suggestion System Facilitates Language Learners’ Emotional Expressions - Chen, Mei-Hua; Chen, Wei-Fan; Ku, Lun-Wei (Proceedings of the AsiaCALL 2014)

Thin Capitalization Rules and Entrepreneurial Capital Structure Decisions - Maßbaum, Alexandra; Sureth-Sloane, Caren (Business Research)

Difference Computation for Grammar-Compressed XML Data - Böttcher, Stefan; Hartel, Rita; Thiele, Sebastian (Proceedings of the Second Australasian Web Conference)

Keyword Search on DAG-Compressed XML Data - Böttcher, Stefan; Brandenburg, Marc; Hartel, Rita (Proceedings of the Second Australasian Web Conference)

Efficient XML Keyword Search Based on DAG-Compression - Böttcher, Stefan; Hartel, Rita; Rabe, Jonathan (Database and Expert Systems Applications - 25th International Conference, DEXA 2014)

Functionally Graded Alloys Obtained by Additive Manufacturing - Niendorf, Thomas; Leuders, Stefan; Riemer, Andre; Brenne, Florian; Tröster, Thomas; Richard, Hans Albert; Schwarze, Dieter (Advanced Engineering Materials)

On the fatigue crack growth behavior in 316L stainless steel manufactured by selective laser melting - Riemer, A.; Leuders, S.; Thöne, M.; Richard, H.A.; Tröster, Thomas; Niendorf, T. (Engineering Fracture Mechanics)

Preference-based learning of ideal solutions in TOPSIS-like decision models - Agarwal, M.; Fallah Tehrani, A.; Hüllermeier, Eyke (Journal of Multi-Criteria Decision Analysis)

Extended graph-based models for enhanced similarity search in Cabase - Krotzky, T.; Fober, T.; Hüllermeier, Eyke; Klebe, G. (IEEE/ACM Transactions of Computational Biology and Bioinformatics)

Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (International Journal of Approximate Reasoning)

Visualization of evolving fuzzy-rule-based systems - Henzgen, Sascha; Strickert, M.; Hüllermeier, Eyke (Evolving Systems)

Preference-based reinforcement learning: evolutionary direct policy search using a preference-based racing algorithm. - Busa-Fekete, Robert; Szörenyi, B.; Weng, P.; Cheng, W.; Hüllermeier, Eyke (Machine Learning)

Open challenges for data stream mining research - Krempl, G.; Zliobaite, I.; Brzezinski, D.; Hüllermeier, Eyke; Last, M.; Lemaire, V.; Noack, T.; Shaker, A.; Sievi, S.; Spiliopoulou, M.; Stefanowski, J. (SIGKDD Explorations)

Correlation-based embedding of pairwise score data - Strickert, M.; Bunte, K.; Schleif, F.M.; Hüllermeier, Eyke (Neurocomputing)

Survival analysis on data streams: Analyzing temporal events in dynamically changing environments - Shaker, Ammar; Hüllermeier, Eyke (International Journal of Applied Mathematics and Computer Science)

Reliable classification: Learning classifiers that distinguish aleatoric and epistemic uncertainty - Senge, Robin; Bösner, S.; Dembczynski, K.; Haasenritter, J.; Hirsch, O.; Donner-Banzhoff, N.; Hüllermeier, Eyke (Information Sciences)

The comprehensive diagnostic study is suggested as a design to model the diagnostic process - Donner-Banzhoff, N.; Haasenritter, J.; Hüllermeier, Eyke; Viniol, A.; Bösner, S.; Becker, A. (Journal of Clinical Epidemiology)

Characterization of the corrosion influence on the fatigue behavior of intrinsic CFRP-steel-hybrids - Klein, M.; Hülsbusch, D.; Walther, F.; Bartsch, M.; Hausmann, J.; Frantz, M.; Lauter, C.; Tröster, Thomas

Efficient manufacturing of hybrid structures consisting of steel and CFRP with using residual heat / Effiziente Herstellung von Hybridbauteilen aus Stahl und CFK mithilfe von Restwärmeausnutzung - Frantz, M; Lauter, Christian; Tröster, Thomas; Hausmann, J.; Bartsch, M.; Hülsbusch, D; Walther, F.

Observing optical coherence across Fock layers with weak-field homodyne detectors - Donati, Gaia; Bartley, Tim; Jin, Xian-Min; Vidrighin, Mihai-Dorian; Datta, Animesh; Barbieri, Marco; Walmsley, Ian A. (Nature Communications)

Crash simulation of high strength automotive components using advanced failure models - Block, Holger; Marten, Thorsten; Tröster, Thomas

Quasistatic and crash tests of steel-CFRP hybrid pillar structures for automotive applications - Lauter, Christian; Niewel, Joerg; Tröster, Thomas (International Journal of Automotive Composites)

Entwicklung und Herstellung von Hybridbauteilen aus Metallen und Faserverbundkunststoffen für den Leichtbau im Automobil - Lauter, Christian

Crash performance of the new press hardenable steel 15MnB6 - Block, Holger; Marten, Thorsten; Weiß Borkowski, Nathalie; Tröster, Thomas

Numerical simulation of the energy absorption of fiber-reinforced plastics - Reuter, Corin; Flore, Dominik; Pöhler, Simon; Sauerland, Kim Henning; Tröster, Thomas

Mehrachsige Werkstoffprüfung bei hoher Dehnrate im Hochgeschwindigkeits-Tiefungsversuch - Weiß Borkowski, Nathalie; Marten, Thorsten; Tröster, Thomas

Selective-Laser-Melting materials under cyclic loading: Influence of process-inherent defects on the initiation and propagation of fatigue cracks - Leuders, S.; Riemer, A.; Richard, H. A.; Tröster, Thomas; Niendorf, T.